Perbandingan Kualitas Pot Hitam dan Softpot Terhadap Pertumbuhan Vegetatif Anggrek Dendrobium sonia ersakul - Devany England Filany; M. Anas Dzakiy; Lussana Rossita Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to compare the quality of black pots and soft pots on the vegetative growth of the Dendrobium sonia ersakul orchid. The method used was perfect randomization with one treatment, namely black pot and soft pot. Data analysis used a two-way t-test at the 5% level. The results of the research show that using different types of pots can make a real difference to the parameters of plant height, length of shoots and number of new roots, but does not make a real difference to root length. The difference in the quality of the two pots is influenced by the level of water supply to the plant, plant drainage, and the level of oxygen absorption in the roots. Keywords: Dendrobium Orchid, Vegetative Growth, Black Pot, Softpot